Faktor-Faktor yang Menentukan Minat Beli Konsumen di Cafe 70's Plate Kitchen Denpasar Bali - Wijaya, Julia Jeansmory; Astina, IB Ketut; Putra, Agus Muriawan (Jurnal Kepariwisataan dan Hospitalitas; Vol 6 No 2 (2022): Vol.6,No.2,2022, 2023)
Cafe 70’s Plate Kitchen officialy opened on 9 February 2019 and located at Raya Sesetan Street No. 174AB, Denpasar. This cafe is a new cafe which need information about consumer characteristics and factors on consumer buying interest to compete with other restaurants. Data source of this research are prime data and secondary data. Variety data are quantitative data and qualitative data. This research use quantitative descriptive as analysis method and Slovin as sampling technique with insidental sampling way to find the sample. This research use 100 respondents. Consumer characteristics based on origins are originated mostly from Bali (70%), mostly from 13-22 years old (64%), mostly women (56%), mostly high school graduate (56%), mostly student (53%), mostly earn under Rp2.500.000 (56%), mostly from friends or family (78%), mostly for hang out (59%), and mostly came by once (67%). Total result of factor analysis of consumer buying interest scores 4,06 with category of good. Indicator of restaurant atmospher scores 4,26 (very good). Food quality scores 4,19 (good), price scores 3,99 (good), service quality scores 3,96 (good), and location scores 3,91 (good). This research use 20 indicators for the questionnaire. There are 6 factors made that attract consumer buying interest which are atmosphere factor, price factor, service quality factor, location factor and location strategy factor. Factor that dominate consumer buying interest at 70’s Plate Kitchen Cafe is atmosphere factor and the factor that least affect consumer buying interest at 70’s Plate Kitchen Cafe is location strategy factor.